USG Guiding Spinal Anesthesia pada Sectio Caesarea - Saputra, Dya; Sudadi, Sudadi; Wisudarti, Calcarina Fitri Retno (Jurnal Komplikasi Anestesi, 2023)
The practice of using central neuraxial block (CNB) techniques is now increasingly being done. In principle, this technique is highly dependent on the palpation of anatomical markings in bones, along with feedback from tactile sensations when inserting needles. Although anatomic landmarks are useful, they are often difficult to find or feel in patients pregnancy with obesity, changes in the patient's anatomical structure, edema in the back, and underlying spinal abnormalities or after spinal surgery. Recent years have seen increasing interest in the use of ultrasound for interventions in regional anesthesia. Ultrasound is non-invasive, safe, easy to use, can be done quickly, does not involve exposure to radiation, provides real-time images, is free of side effects, and may also be beneficial in pregnancy with obesity and abnormal spinal anatomy